Heritage at risk: understanding conservation practice for studio dilapidation studies - Ab Jalil, Nurlelawati (Nova Science Publisher, Inc., 2025)
On-site learning is a practical and vital method for students in built environment programs to develop their professional skills in the heritage conservation field. The process enables students to actively observe tangible realities in conservation work since it offers a deeper understanding of the properties of historical materials, construction techniques, the embedded cultural significance and, most importantly, the appropriate way to document building conditions. The practices involved in heritage conservation, which are guided by both local regulations and international standards, are used as a framework to ensure the structural integrity of a heritage building, while protecting the identity of the place and its continuity. This framework contributes to the structured workflow that covers the main stages and processes in the preservation, restoration and management of historical structures. It is also essential that the framework be embedded in the learning process to gain an optimal learning experience and understanding of the importance of its stages in comprehensive efforts to protect heritage assets. Drawing from such a framework of practices, this chapter aimed to elaborate on how on-site learning enriches the teaching and learning of studio-based projects in heritage conservation, particularly in dilapidation studies for the rehabilitation and regeneration of traditional Malay buildings. © 2025 Nova Science Publishers, Inc.